Configurations of New Public Management reforms and the efficiency, effectiveness and equity of public healthcare systems: a fuzzy-set Qualitative Comparative Analysis. Issue 8 (3rd August 2019) - Andrews, Rhys; Beynon, Malcolm J.; McDermott, Aoife
ABSTRACT: Fuzzy-set Qualitative Comparative Analysis identifies configurations of New Public Management (NPM) reforms (privatization, consumerism, performance management, and corporatization) associated with perceptions of improvements in healthcare efficiency, effectiveness and equity in 14 European countries. Although these outcomes are pursued concurrently, no combination of the considered reforms appears to support success or failure across the board and the inter-relations between reforms shape their effects. Three NPM reform profiles are evident in Europe; (1) strong reformers, adopting a comprehensive package of reforms that are perceived to perform better than (2) partial reformers, with (3) limited reformers also doing better than partial reformers.